Avaliação de moléculas de clorofilas e seus derivados em espécies de microalgas cultivadas em fotobiorreatores - Fernandes, Andrêssa Silva (2017)
Microalgae are photosynthetic microorganisms, which, in turn, present great potential for insertion in biotechnological processes with the parallel production of biomolecules, such as chlorophylls that are abundantly present in microalgal biomass. However, detailed studies on the complete characterization of the qualitative and quantitative profile of chlorophyll biomolecules in microalgae species are scarce in the literature. The objective of this work was to evaluate the profile of chlorophylls profile in extracts of Scenedesmus obliquus, Chlorella vulgaris and Aphanothece microscopica Nägeli grown in photobioreactors. The total chlorophylls content, based on the dry weight of the biomass, of Scenedesmus obliquus, Chlorella vulgaris and Aphanothece microscopica Nägeli were 7,319.0 μg.g-1, 10,734.1 μg.g-1 and 9,121.8 μg.g-1, respectively. A total of ten different chlorophylls compounds were separated in all the extracts, the major ones being chlorophyll a (47.0%) and pheophytin a' (21.8%) in Scenedesmus; chlorophyll a (57.0 %) and chlorophy a' (14.9 %) in Chlorella; pheophytin a' (35.8 %) and chlorophyll a (26.6 %) in Aphanothece. Besides these compounds, it was possible to identify hidroxychlorophyll a', chlorophyll b, chlorophyll b', 15-Hydroxy-lactone chlorophyll a, hidroxypheophytin a, hidroxypheophytin a' and pheophytin a. The results obtained evidenced that the three species of microalgae are promising alternatives for obtaining natural chlorophyll compounds, since they presented a qualitative and quantitative profile relevant for biotechnological exploration. In addition, the book chapter "Carotenoids in microalgae" (Chapter 3) was published as a complementary research to this work.